2017
DOI: 10.18203/2349-3933.ijam20175082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of patients with thrombocytopenia at tertiary health care centre

Abstract: Background: In tropical countries like India thrombocytopenia is commonly encountered by clinicians in any speciality. Thrombocytopenia present as asymptomatic condition to sometimes becomes a life-threatening condition requiring blood transfusion in various etiological conditions. Infections like malaria and dengue are invariably associated to thrombocytopenia with changing trends in clinical features. Infection is the commonest cause of thrombocytopenia. The objective of study was to evaluate the different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Among all the study populations, 6.1% of patients had septicemia. Patne et al, Gondhali et al, Modi et al, and Raikar et al had similar findings to this study that viral infection like dengue fever is the most common cause of febrile thrombocytopenia [ 3 , 14 - 16 ], whereas Gandhi et al and Kumbhar et al found malaria as the common etiology for fever with thrombocytopenia [ 17 - 19 ]. Other rare causes include septicemia, enteric fever, and hematological malignancy like ALL.…”
Section: Discussionsupporting
confidence: 83%
“…Among all the study populations, 6.1% of patients had septicemia. Patne et al, Gondhali et al, Modi et al, and Raikar et al had similar findings to this study that viral infection like dengue fever is the most common cause of febrile thrombocytopenia [ 3 , 14 - 16 ], whereas Gandhi et al and Kumbhar et al found malaria as the common etiology for fever with thrombocytopenia [ 17 - 19 ]. Other rare causes include septicemia, enteric fever, and hematological malignancy like ALL.…”
Section: Discussionsupporting
confidence: 83%
“…Other bleeding manifestations included haemoptysis in three (5%) patients, haematuria in two (3.33%), and epistaxis in two (3.33%) patients. According to PatneSV et al, bleeding manifestations were present in 37.50% of patients, and the most common site of bleeding was the skin and mucous membrane [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to PatneSV et al, bleeding manifestations were present in 37.50% of patients, and the most common site of bleeding was the skin and mucous membrane [11].…”
Section: Figure 3: Haemorrhagic Manifestations Associated With Thromb...mentioning
confidence: 99%
“…The study conducted by Patne et al showed that thrombocytopenia was caused due to infections in 63.33% patients [9]. Considering p= 0.6333, q= 0.3667, Z=1.96 for confidence level of 95% and d (absolute precision) = 0.1, sample size was calculated to be 92.…”
Section: Sample Size Calculationmentioning
confidence: 99%